2015
DOI: 10.1111/bju.13024
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal template‐guided prostate biopsy: 10 years of experience

Abstract: Objective• To assess the efficacy and safety of transperineal templateguided prostate biopsy. Materials and Methods• From December 2003 to December 2013, a total of 3 007 patients (30-91 years old, mean age 69.1) who met the inclusion criteria underwent 11-region transrectal ultrasound-guided transperineal template prostate biopsy.• The inclusion criteria included a prostate-specific antigen (PSA) level of 4.0 ng/mL or greater and abnormal prostate gland findings on digital rectal examination, ultrasound, CT o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Over the past 10 years, we have completed more than 5000 cases of template-guided transperineal prostate biopsies and proposed our own perspective regarding the spatial distribution of prostate cancer on prostate biopsy [ 4 6 ]. Confirmation using radical prostatectomy specimens is the most reliable method for verifying the accuracy of template-guided transperineal prostate biopsy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10 years, we have completed more than 5000 cases of template-guided transperineal prostate biopsies and proposed our own perspective regarding the spatial distribution of prostate cancer on prostate biopsy [ 4 6 ]. Confirmation using radical prostatectomy specimens is the most reliable method for verifying the accuracy of template-guided transperineal prostate biopsy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These misses might have occurred because larger prostates may be shielded by the pubic arch. [ 8 ] To avoid this, we did not use the template and punctured obliquely upward in patients with pubic arch occlusion, [ 8 ] which however, lowered the accuracy. The efficacy of biopsy in this area would be enhanced with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…TTPSB was performed in 11 regions. [ 8 ] The Bard Biopsy gun (C.R. Bard, Inc., Covington, GA) and an 18-gauge biopsy needle were used to obtain biopsy cores transperineally through the template.…”
Section: Methodsmentioning
confidence: 99%
“…However, our study reported the 39.3% PCDR, higher than that of study by Mai et al . (35.5%) [17]. The difference was possibly originated from different inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%